2005
DOI: 10.2337/diacare.28.6.1431
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Early-Onset Age of Type 1 Diabetes on Cerebral Structure and Cognitive Function

Abstract: OBJECTIVE -Children who develop type 1 diabetes before age 7 years (early-onset diabetes; EOD) have comparatively poorer cognitive abilities. Whether this relates to psychosocial consequences of chronic illness or organic factors related to diabetes and its complications remains unresolved. We hypothesized that if differences in neuroradiological structure and cognitive ability coexisted in those who had EOD, then an organic component to their etiology was likely. RESEARCH DESIGN AND METHODS-A cohort of 71 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
150
4
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(171 citation statements)
references
References 45 publications
9
150
4
8
Order By: Relevance
“…Results showed an association between decreased brain volume and slowing of information processing speed, reduced attention, and lower IQ subtest scores (12,13). Furthermore, smaller brain volumes in patients were related with poor metabolic control, reflected by chronic hyperglycemia (9,12) and hypoglycemic events (9,10).…”
Section: Type 1 Diabetesmentioning
confidence: 89%
“…Results showed an association between decreased brain volume and slowing of information processing speed, reduced attention, and lower IQ subtest scores (12,13). Furthermore, smaller brain volumes in patients were related with poor metabolic control, reflected by chronic hyperglycemia (9,12) and hypoglycemic events (9,10).…”
Section: Type 1 Diabetesmentioning
confidence: 89%
“…The hippocampus has also been implicated in neurocognitive dysfunction in children and adolescents with type 1 diabetes, particularly in those with a younger age of type 1 diabetes onset. Ferguson et al [104] found an increased number of hippocampal small punctuate white matter lesions in those with early-onset diabetes (onset younger than 7 years of age). This finding is consistent with a recent study by Ho et al [105] that identified mesial temporal lobe sclerosis more frequently in individuals with early-onset vs later onset of type 1 diabetes.…”
Section: Neurobiological Factorsmentioning
confidence: 99%
“…; la frecuencia de las hipoglucemias severas estaba relacionada significativamente con el tiempo de reacción y con el umbral de rapidez de procesamiento de la información visual; en una muestra con una distribución normal en las puntuaciones obtenidas en C.I. las medidas de inteligencia correlacionaban significativamente con tests cognitivos elementales, especialmente en tareas de procesamiento visual (Deary, et al, 1992 (Ferguson et al 2005). …”
Section: Desarrollo Intelectualunclassified